Calling out liars: five minutes with . . . Jed Mercurio. (10th December 2021) - Mahase, Elisabeth
Abstract : Screenwriter and former doctor Jed Mercurio—famous for TV shows such as Line of Duty and Bodyguard —talks about corruption, lies, and holding people in power during the pandemic to account